Republic of Lithuania : Third Review Under the Stand-by Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper focuses on the Republic of Lithuania's Third Review Under the Stand-By Arrangement. Program implementation has been good and all end-December 2002 quantitative performance criteria were met. Macroeconomic performance in 2002 was better than expected: real GDP grew by 5.9 percent, led by domestic demand. Further progress was made in structural reforms during 2002, including tax reform, municipal finances, health care expenditure, banking privatization, financial sector reforms, and energy sector privatization. Some measures, however, were implemented with some delays, including privatization in the energy sector.